An Unknown Early Modern New World Epic: Girolamo Vecchietti's Delle prodezze di Ferrante Cortese (1587–88). (14th January 2019) - Cox, Virginia
Abstract: This article discusses an unpublished vernacular Italian New World epic of the 1580s, which narrates the Spanish conquest of Mexico. The work was authored by the traveler, diplomat, and Orientalist Girolamo Vecchietti, and it is dedicated to Ferdinando I de' Medici, grand duke of Tuscany. Vecchietti's poem is striking as a rare epic in terza rima, and as the sole surviving early modern Italian epic to center on the deeds of Cortés, rather than Columbus or Vespucci. It is also intriguing for its ambivalent attitude toward the Spanish colonizing enterprise, portrayed initially as a heroic evangelizing mission, but later shown in a more compromised light.